"Análisis de la disponibilidad y demanda hídrica en el Sistema de Riego Paquishapa - Maldonado Soto, Paola Nicole (2018)
The research project is located in the Urdaneta parish, canton Saraguro that belongs to the province of Loja; This project intended to carry out the water supply analysis of the Ramas micro-basin, which supplies the Paquishapa irrigation system, and the existing demand in the irrigation area and thereby be able to know if the demand is significant with respect to the supply, and be able to generate a proposal for the optimization of water resources so that they are not misused and agriculture is developing. To determine the water availability of the microbasin Ramas, it began with morphometric analysis, which gives a broad view of the conditions of the microbasin Branches in shape, relief and density of drainage, it should be noted that this project was developed in large part with the application of GIS software applied to the water study. For the generation of precipitation and flows, the meteorological stations of: Saraguro, San Lucas, Oña and Yantzaza were selected; the respective analysis was performed to apply empirical methods to estimate precipitation and average monthly flows, in addition the direct gauging method was applied with the windmill in the Ramas stream, to corroborate the empirically estimated flows, the surveys were performed twice a month during the During this period, the empirical methods applied to determine the average monthly flows were: curve number, ecological polynomial, and rational method, by means of the flow-time graph, in which each of the applied methods influences. selected the ecological polynomial method since it was the one with the best tendency with the direct method. The demand was obtained through the property cadastre of the irrigation area, the area and crops developed in this area were determined, the Kc index of the crop was obtained for each development period using the FAO book 56, in set with reference evapotranspiration evapotranspiration of each culture was obtained by this precipitation and the effective area of irrigation water demands of the sector were obtained. The analysis between the demand versus the supply, indicates that the demand has a shortage index of 1%, that is to say that the demand is very low with respect to the offer. And a general proposal was made to expand the irrigation area by 500%, that is, from 79 hectares at present to 452 hectares. Once again, each parameter was determined, which allows us to know the demand of this new irrigation area, such as the cultivation coefficient, evapotranspiration of each crop and effective precipitation, to know the demand that these have. The new demand versus the supply was analyzed again, resulting in a shortage index of 10%, although it was still in the category of very low demand with respect to supply. So it can be considered that the Paquishapa irrigation system is oversized for the demand that requires the place of study.